STUDI SEDIMENTASI PADA DAS SEUNAGAN KABUPATEN NAGAN RAYA - Dian Safiana; Eldina Fatimah; Azmeri Azmeri (Prodi Magister Teknik Sipil Unsyiah, 2019)
Seunagan River Basin Area has a very important role as a water needs for the people in Nagan Raya Regency and the half of West Aceh Regency. The condition of Krueng Seunagan River Basin Area is getting more and more critical which is marked by a lot of dangerous activities inside and outside the River Basin Area such as mining, land conversion and so on. This study aim are for knowing how much a yearly sediment production that happened in Krueng Seunagan River Basin Area and the Sediment Delivery Ratio (SDR) and also to recommend the effort of land conservation. From the sediment rate analysis in Sub River Basin Areas, it obtained variation sediment rate that spread over 4 Sub River Basin Areas. From the yearly sediment production analysis result can be confirmed that the largest sediment production happened in Seunagan Hulu Sub River Basin Area, which the sediment production is 143.879,08 ton/year and then followed by Seunagan Hilir Sub River Basin Area 135.644,02 ton/year, and then Cut Sub River Basin Area 116.016,74 ton/year and the smallest sediment production happened in Isep Sub River Basin Area which the sediment production is 107.985,52 ton/year. The Sediment Delivery Ratio (SDR) result for each sub river basin area is Seunagan Hulu 9,6%, Isep 12,2 %, Cut 11,8% and Seunagan Hilir 10,0 %